LABORATORY DIAGNOSIS AND TREATMENT OF MYCOPLASMA PNEUMONIAE INFECTION IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Mycoplasma pneumoniae (MP) is the cause of Mycoplasma pneumoniae pneumonia (MPP) in children and adolescents, with the clinical manifestations highlighted by intermittent irritating cough, accompanied by headache, fever and muscle pain. This paper aimed to study the research status and focal points in MP infection, especially the common laboratory diagnostic methods and clinical treatment of Mycoplasma pneumoniae. Laboratory diagnostic methods include molecular assay, serological antibody detection, rapid antigen detection and isolation and culture. Polymerase chain reaction (PCR) is the gold standard with high sensitivity and specificity. The serological antibody can detect various immune antibodies qualitatively or quantitatively in serum. Rapid antigen can be detected faster, with no equipment environment requirements, which can be used for the early diagnosis of MP infection. While the culture growth cycle is long and insensitive, not recommended for routine diagnosis.